Percepção de estudantes sobre utilização de métodos de aula invertida no ensino de gerenciamento de enfermagem - TRINDADE, Ricky Falcão Silva (2019)
This is a descriptive study with a qualitative approach carried out in a nursing faculty of a public university located in the northern region of Brazil. The undergraduate course effectively investigated was the one of Administration in Nursing, inserted in the fifth semester of the course, where the activities were developed integrally by the Flipped Classroom model, in this study is adopted the free translation: inverted class. They were used during the discipline: Peer Instruction, Just-in-Time-Teaching and Team Based Learning, taking into account the program content and its objectives. Participants were 8 undergraduate students regularly enrolled in the fifth semester of nursing in the second semester of 2017. The class consisted of 29 students, with participants selected from the following inclusion criteria having attendance in classes ≥ 75% and at least 70% of the activities per unit of the discipline. Data collection was done through a semistructured interview. For the data analysis, the open and axial coding phases of the constant comparisons method (STRAUSS; CORBIN, 2008) were used. It was ordered in a trial version of the program Atlas TI®. At the end of the open coding were generated 22 codes grouped, during the axial codification, in 5 families which will be called categories to facilitate the understanding, being the categories: Preferences: where it was observed that the previous reading is considered by a part of the participants as an important strategy for learning and affirmations that suggest students' understanding that there are better teaching strategies and methods for each content and / or context; Inverted Classroom - The students' perception, where it was observed that students have an understanding about the elements of the inverted classroom model. Each method generated a set of differentiated affirmations, for example, Just-in-Time-Teaching, a series of statements about students' knowledge needed by the teacher to develop it; Improved learning process in student perception, where the students described the development or exercise of autonomy in relation to the learning process. TBL was the method most commented by the participants and preferred; Difficulties and Challenges, where the challenge of working with a teaching method different from conventional teaching methods, that is, the challenge of going through a process of change, has been observed, difficulties related to the methods used, such as need for previous reading that proved to be laborious for some students, difficulty accessing materials through e-mail, difficulty or lack of access to the internet, there were difficulties that are not related to the model, it is worth noting the difficulty of reconciling the activities of all the curricular activities of the semester, suggesting that there was no integration in the construction of the planning of all curricular activities of the semester; Suggestions and evaluations, where students evaluated themselves most of the time positively commenting on their behavior and performance throughout the course, regarding the didactic-methodological strategies the assessments were a little more critical, suggesting that students have easier to critically evaluate teachers than themselves and it was possible to observe that some students were more critical than the others, despite the fact that the same pedagogical model has been worked out for all, this leads to the following reflection: the pedagogical experience is personalized.